Seasonal Tracer Subduction in the Subpolar North Atlantic Driven by Submesoscale Fronts - Picard, Théo; Gula, Jonathan; Vic, Clément; Mémery, Laurent (Journal of Geophysical Research: Oceans, 2024)
International audience Submesoscale flows (0.1–10 km) are often associated with large vertical velocities, which can have a significant impact on the transport of surface tracers, such as carbon. However, global models do not adequately account for these small‐scale effects, which still require a proper parameterization. In this study, we introduced a passive tracer into the surface mixed layer (ML) of a northern Atlantic Ocean simulation based on the primitive‐equation model CROCO, with a horizontal resolution of Δ x = 800 m, aiming to investigate the seasonal submesoscale effects on vertical transport. Using surface vorticity and strain rate criteria, we identified regions with submesoscale fronts and quantified the associated subduction, that is the export of tracer below the ML depth. The results suggest that the tracer vertical distribution and the contribution of frontal subduction can be estimated from surface strain and vorticity. Notably, we observed significant seasonal variations. In winter, the submesoscale fronts contribute up to 40% of the total vertical advective transport of tracer below the ML, while representing only 5% of the domain. Conversely, in summer, fronts account for less than 1% of the domain and do not contribute significantly to the transport below the ML. The findings of this study contribute to a better understanding of the seasonal water subduction due to fronts in the region.